Yorkshire Royalist Composition Papers, Volume 2 Or the Proceedings of the Committee for Compounding with Deliquents during the Commonwealth - Clay, John William (Cambridge library collection. British & Irish History, 17th & 18th Centuries, 1895)
To raise money for the Parliamentarian cause in the English Civil War, from 1645 the Committee for Compounding with Delinquents assessed the property of Royalist supporters and fined them, the rate depending on their degree of involvement, their religion and profession. The fine varied between a tenth and two thirds of their assets. They were also forced to take an oath to support Parliament, and could lose their estates if they re-offended or failed to pay the fine in full. Edited by John William Clay (1838–1918) and published between 1893 and 1896, this three-volume collection contains all the entries in the archives relating to Yorkshire landholders. Volume 2 (1895) contains abstracts of cases 71–312, dating from 1646 to 1649. This remains an important historical source on Yorkshire during the Civil War period